Electromagnetic transients in transformer and rotating machine windings - Su, Qi (Information Science Reference, 2013)
"This book explores relevant theoretical frameworks, the latest empirical research findings, and industry-approved techniques in this field of electromagnetic transient phenomena"--Provided by publisher.